Luminescent Lanthanide Infinite Coordination Polymers for Ratiometric Sensing Applications - Ziqin Song; Yuanqiang Hao; Yunfei Long; Peisheng Zhang; Rongjin Zeng; Shu Chen; Wansong Chen (Molecules)
Ratiometric lanthanide coordination polymers (Ln-CPs) are advanced materials that combine the unique optical properties of lanthanide ions (e.g., Eu3+, Tb3+, Ce3+) with the structural flexibility and tunability of coordination polymers. These materials are widely used in biological and chemical sensing, environmental monitoring, and medical diagnostics due to their narrow-band emission, long fluorescence lifetimes, and excellent resistance to photobleaching. This review focuses on the composition, sensing mechanisms, and applications of ratiometric Ln-CPs. The ratiometric fluorescence mechanism relies on two distinct emission bands, which provides a self-calibrating, reliable, and precise method for detection. The relative intensity ratio between these bands varies with the concentration of the target analyte, enabling real-time monitoring and minimizing environmental interference. This ratiometric approach is particularly suitable for detecting trace analytes and for use in complex environments where factors like background noise, temperature fluctuations, and light intensity variations may affect the results. Finally, we outline future research directions for improving the design and synthesis of ratiometric Ln-CPs, such as incorporating long-lifetime reference luminescent molecules, exploring near-infrared emission systems, and developing up-conversion or two-photon luminescent materials. Progress in these areas could significantly broaden the scope of ratiometric Ln-CP applications, especially in biosensing, environmental monitoring, and other advanced fields.